العنف في الوسط الجامعي: الأسباب والحلول من وجهة نظر طلبة جامعة الشهيد حمه لخضر بالوادي - جلول, أحمد (University of Eloued جامعة الوادي, 2016)
هدفت الدراسة إلى التعرف على أسباب العنف في الوسط الجامعي والحلول الممكنة من وجهة نظر طلبة جامعة الشهيد حمه لخضر بالوادي حسب متغيري الجنس والمستوى الدراسي، وقد تكونت عينة الدراسة من (279) طالبا وطالبة خلال الموسم الجامعي 2014/2015، وتم استخدام أداة أسباب العنف في الوسط الجامعي وأداة الحلول المقترحة للحد منه من وجهة نظر الطلبة، وقد دلت النتائج على أن ضعف الوازع الديني لدى الطلبة وشعورهم بعدم المساواة بين الطلبة وعدم كفاءة الإجراءات التأديبية في ردع بعض المخالفات التي يرتكبها الطلبة داخل الجامعة من أكثر أسباب العنف في الوسط الجامعي، كما دلت النتائج كذلك على أن تجنب التمييز بين الطلبة ورفع وعيهم حول قوانين الانضباط وقيام الأمن بواجباته وإقامة العلاقات الإيجابية بين الطلبة وأعضاء هيئة التدريس من أكثر الإجراءات التي يمكنها أن تحدّ أو تقلّل من العنف في الوسط الجامعي، ولم تظهر فروق ذات دلالة إحصائية في أسباب العنف والحلول المقترحة للحد من العنف في الوسط الجامعي تبعا لمتغيري الجنس والمستوى الدراسي. ABSRACT The present study aimed to identify the causes of violence in the university milieu and the possible solutions from the viewpoint of Hamma Lakhdar University students according to sex, academic level variables. The study sample consisted of 279 male and female students during the academic year 2014/2015.Causes of violence in the university milieu and proposed solutions from students perspective measures were used in the study. The findings showed that the weakness of the religious influence of the students and their feeling of inequality among them and also the inefficiency of the disciplinary measures to deter some of the irregularities committed by students in the university were of the most causes of violence in the university milieu. The results also indicated avoidance of discrimination between students, raising their awareness about the discipline laws, doing security duties and establishing positive relationships between students and members of teaching staff are the most effective procedures that could limit or reduce the violence in the university milieu. The results didn't show any statistically significant differences in the causes of violence and the proposed solutions to reduce violence in the university milieu depending on sex and academic level variables
Violence - university - students – El-oued - education.
مجلة البحوث والدراسات المجلد 13 العدد 02 جامعة الوادي
Keywords: العنف- الجامعة- الطلبة- الوادي- التربية; Violence - university - students – El-oued - education